France's War in Mali Lessons for an Expeditionary Army - Shurkin, Michael (RAND Corporation, 2014)
This report discusses the 2013 French Army operations in Mali (Operation Serval) to provide a model for an expeditionary force that has attributes and competencies the United States Army seeks. The French demonstrated that they are adept at fielding small yet capable forces tailored for specific objectives and reiteratively task organizing as the situation evolves. They also have a culture and force structure geared for expeditionary operations.